A new species of the snake genus Fimbrios from Phong Nha-Ke Bang National Park, Truong Son, central Vietnam (Squamata: Xenodermatidae) - Ziegler, Thomas; David, Patrick; Miralles, Aurelien; van Kien, Doan; Truong, Nguyen Quang (Zootaxa, 2008)
A second species of the previously monotypic snake genus Fimbrios is described from the Truong Son Mountain Range, Vietnam. Fimbrios smithi sp. n. is included in this genus on the basis of the combination of the following characters: rostral, mental and first three to four labials with raised, erected edges; a horizontal ridge of tissues above the rostral; a very large loreal. It is distinguished from F. klossi by having the suture between the internasals longer than that between the prefrontals; two suboculars; 193 ventrals, and 72 unpaired subcaudal scales; total length of at least 440 mm in males (with a tail length of 94 mm, and a tail / total length ratio of 0.214); dorsum greyish brown, with a paler flank area, and pale blotches and stripes in the neck region. Fimbrios smithi sp. n. is the seventh snake species that has been described as new from the Phong Nha—Ke Bang National Park, Quang Binh Province, central Vietnam, in the last decade; it is the forty-fourth colubrid snake species known from that region, which now comprises 60 snake species in general.